2017
DOI: 10.3390/w9090669
|View full text |Cite
|
Sign up to set email alerts
|

Debris Flow Susceptibility Assessment in the Wudongde Dam Area, China Based on Rock Engineering System and Fuzzy C-Means Algorithm

Abstract: Debris flows in the Wudongde dam area, China could pose a huge threat to the running of the power station. Therefore, it is of great significance to carry out a susceptibility analysis for this area. This paper presents an application of the rock engineering system and fuzzy C-means algorithm (RES_FCM) for debris flow susceptibility assessment. The watershed of the Jinsha River close to the Wudongde dam site in southwest China was taken as the study area, where a total of 22 channelized debris flow gullies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The qualitative model assigns a weight (0-1) to each debris flow triggering factor based on expert experience and knowledge or heuristics to assess the DFS [9]. Common qualitative analysis methods include fuzzy logic [10], analytic hierarchy [11] and network analysis [12] and so on. While these models have achieved a lot in the study of debris flows, they still suffer for some shortcomings, such as a high degree of subjectivity and limited applicability to specific areas [13].…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative model assigns a weight (0-1) to each debris flow triggering factor based on expert experience and knowledge or heuristics to assess the DFS [9]. Common qualitative analysis methods include fuzzy logic [10], analytic hierarchy [11] and network analysis [12] and so on. While these models have achieved a lot in the study of debris flows, they still suffer for some shortcomings, such as a high degree of subjectivity and limited applicability to specific areas [13].…”
Section: Introductionmentioning
confidence: 99%
“…The RF model, which can analyze the importance of classification features and determine the weight of each controlling factor, is a classification model that is composed of many decision trees [ 54 , 55 ]. The RF model includes two main kinds of algorithms: the GINI index algorithm and the out-of-bag (OOB) error rate replacement algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…e Bayesian network model for debris flow prediction was proposed by Banihabib et al [10], and this research indicated that average basin elevation, watershed area, current rainfall, and discharge of 1 day ago are the effective predictors in forecasting debris flows. e application of the fuzzy C-means algorithm in the risk assessment of debris flow has also achieved more reliable results [11].…”
Section: Introductionmentioning
confidence: 99%